Some Long-Run Correlations of Inflation in Developed Countries - West, Kenneth D. (2022)
Using 100+ years of data from 18 developed countries, we use a frequency domain technique to compute “long-run” correlations between inflation on the one hand and money growth and nominal interest rates on the other. The estimated long-run correlations are almost always positive. Their magnitude is relatively substantial for money growth, more modest for interest rates. We conclude that some traditional propositions about monetary neutrality are broadly consistent with the data.